'TO IMPERISHABLE MEMORY': LANCASTER'S CRIMEAN WAR MONUMENT, c.1855–1862. (7th December 2022) - Edwards, Sam
Abstract : This article examines the previously neglected history of Lancaster's Crimean War monument, dedicated in November 1860. It connects the monument to two key features of the town's mid-century history: Tory paternalism and a resurgent popular patriotism linked to the contemporary 'Volunteer Movement'. It also establishes the broader significance of the structure, especially in terms of British approaches to war commemoration. In particular, it argues that a key feature of the monument—it carries the names of nineteen of the town's servicemen, all rank and file—complicates the generally accepted chronology of when interest in commemorating the 'common soldier' first emerged in Britain. In this sense, Lancaster's Crimean War monument is one of several mid- and late-Victorian monuments, as the Boer War took place in the later Victorian period, that anticipated the defining quality of war remembrance in the post-1918 period, what Thomas Laqueur has called 'necronominalism' (that is, the naming of the dead, regardless of class or status). The monument is thus indicative of Lancaster's mid-century social politics and it also nuances, usefully, key details regarding the history of British war commemoration.